2020
DOI: 10.1186/s12959-020-00250-x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation abnormalities in SARS-CoV-2 infection: overexpression tissue factor

Abstract: Among the pathways and mediators that may be dysregulated in COVID-19 infection, there are proinflammatory cytokines, lymphocyte apoptosis, and the coagulation cascade. Venous and arterial thromboembolisms also are frequent in COVID-19 patients with the increased risk of some life-threatening complications such as pulmonary embolism, myocardial infarction, and ischemic stroke. In this regard, overproduction of proinflammatory cytokines such as IL-6, IL-1β, and TNF-α induce cytokine storms, increase the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
3
31
1
2
Order By: Relevance
“…For example, Adams et al (2019) showed that P. gingivalis and bacteria translocated into blood can drive hypercoagulation. However, SARS-CoV-2 also secretes products/proteins that modulate blood clotting cascades ( Eslamifar et al, 2020 ). Pretorius et al (2020a , b , 2021) identified fibrinolytic resistant amyloid microclots in COVID-19 plasma ( Figure 4 ) and in plasma samples collected from 11 PASC subjects.…”
Section: Microbiome Dysbiosis Can Disrupt Host Metabolic and Neuroendocrine Signaling And/or Epithelial Barrier Functionmentioning
confidence: 99%
“…For example, Adams et al (2019) showed that P. gingivalis and bacteria translocated into blood can drive hypercoagulation. However, SARS-CoV-2 also secretes products/proteins that modulate blood clotting cascades ( Eslamifar et al, 2020 ). Pretorius et al (2020a , b , 2021) identified fibrinolytic resistant amyloid microclots in COVID-19 plasma ( Figure 4 ) and in plasma samples collected from 11 PASC subjects.…”
Section: Microbiome Dysbiosis Can Disrupt Host Metabolic and Neuroendocrine Signaling And/or Epithelial Barrier Functionmentioning
confidence: 99%
“…SARS-CoV-2 infection often has dramatic consequences for the circulatory system ( Tang et al, 2020b ), with preliminary reports including thrombocytopenia, elevated d-dimer levels, prolonged prothrombin time, and disseminated intravascular coagulation ( Han et al, 2020 ). Interestingly, research findings suggest that inhibition of TF-FVIIa complex may reduce the cytokine storm responsible for the increased coagulation and multi-organ failure, and thus the mortality rate in COVID-19 patients ( Geisbert et al, 2003 ; Eslamifar et al, 2020 ). Our in silico findings suggested that DB04758 could also bind with high affinity to the SARS-CoV-2 M pro .…”
Section: Resultsmentioning
confidence: 99%
“…In severe COVID-19 patients, increased platelet activation with P-selectin expression and aIIb/b3 signaling gave rise to platelet aggregation with monocytes followed by increased tissue factor expression on monocytes (118). Moreover, D-dimer levels showed significant correlations with platelet activation for P-selectin and monocyte tissue factor expression (118), which indicate that platelet activation-induced tissue factor expression on monocytes is associated with COVID-19 coagulopathy, leading to DIC in critical cases (10,119).…”
Section: Plateletsmentioning
confidence: 98%